Serum DKK1 as a protein biomarker for the diagnosis of hepatocellular carcinoma: a large-scale, multicentre study - Shen, Qiujin; Fan, Jia; Yang, Xin-Rong; Tan, Yexiong; Zhao, Weifeng; Xu, Yang; Wang, Ning; Niu, Yongdong; Wu, Zheng; Zhou, Jian; Qiu, Shuang-Jian; Shi, Ying-Hong; et al. (The lancet oncology, 2012)
Hepatocellular carcinoma (HCC) is prevalent worldwide and improvements in timely and effective diagnosis are needed. We assessed whether measurement of Dickkopf-1 (DKK1) in serum could improve diagnostic accuracy for HCC. We analysed data for patients with HCC, chronic hepatitis B virus (HBV) infection, liver cirrhosis, and healthy controls, recruited from two Chinese centres between December, 2008, and July, 2009. A validation cohort matched for age and sex was recruited from another centre in China between February, 2009, and June, 2011. DKK1 was measured in serum by ELISA by independent researchers who had no access to patients' clinical information. We used receiver operating characteristics (ROC) to calculate diagnostic accuracy. We assessed serum DKK1 in 831 participants: 424 with HCC, 98 with chronic HBV infection, 96 with cirrhosis, and 213 healthy controls. The validation cohort comprised 453 participants: 209 with HCC, 73 with chronic HBV infection, 72 with cirrhosis, and 99 healthy controls. Levels of DKK1 in serum were significantly higher in patients with HCC than in all controls. ROC curves showed the optimum diagnostic cutoff was 2·153 ng/mL (area under curve [AUC] 0·848 [95% CI 0·820–0·875], sensitivity 69·1%, and specificity 90·6% in the test cohort; 0·862 [0·825–0·899], 71·3%, and 87·2% in the validation cohort). Similar results were noted for early-stage HCC (0·865 [0·835–0·895], 70·9%, and 90·5% in the test cohort; 0·896 [0·846–0·947], 73·8%, and 87·2% in the validation cohort). Furthermore, DKK1 maintained diagnostic accuracy for patients with HCC who were α-fetoprotein (AFP) negative (0·841 [0·801–0·882], 70·4%, and 90·0% in the test cohort; 0·869 [0·815–0·923], 66·7%, and 87·2% in the validation cohort), including for patients with early-stage HCC (0·870 [0·829–0·911], 73·1%, and 90·0% in the test cohort; 0·893 [0·804–0·983], 72·2%, and 87·2% in the validation cohort), compared with all controls. Raised concentrations of DKK1 in serum could differentiate HCC from chronic HBV infection and cirrhosis (0·834 [0·798–0·871], 69·1%, and 84·7% in the test cohort; 0·873 [0·832–0·913], 71·3%, and 90·6% in the validation cohort). Moreover, measurement of DKK1 and AFP together improved diagnostic accuracy for HCC versus all controls compared with either test alone (0·889 [0·866–0·913], 73·3%, and 93·4% in the test cohort; 0·888 [0·856–0·920], 78·5%, and 87·2% in the validation cohort). DKK1 could complement measurement of AFP in the diagnosis of HCC and improve identification of patients with AFP-negative HCC and distinguish HCC from non-malignant chronic liver diseases. National Key Basic Research Programme of China, National Key Sci-Tech Special Projects of Infectious Diseases, National Natural Science Foundation of China, Research Fund for the Doctoral Programme of Higher Education of China.